The effect of different tonsillectomy techniques on taste sensation in the early and late postoperative periods - Erol, Zeynep Nur; Türk, Bilge; Seyhun, Nurullah; Cankaya, Mahmut; Altundağ, Aytuğ; Uslu, Berna (The European Research Journal, 2021)
Objectives: Impairment in taste sensation is a rare complication of tonsillectomy. We aimed to reveal the effects of different tonsillectomy techniques on taste sensation by assessing the impairment in taste sensation in the early and late postoperative periods.Methods: In this prospective clinical study, fifty-seven (22 females, 35 males, mean age, 25 ± 9.8 years) patients who underwent tonsillectomy were included. All patients were operated on under general anesthesia, and a chemical stimulation taste test was performed one week prior to the surgery, at first week and first month postoperatively. Four basic taste sensations were assessed in the test (sweet, sour, salty, and bitter), and impairments in taste sensation in the early and late postoperative periods for each tonsillectomy technique were evaluated. Results: In the early postoperative period, there was a statistically significant increase bitter taste sensations in patients who underwent tonsillectomy (p = 0.020). In the late postoperative period, sour and bitter taste sensations were significantly increased in the patients (p = 0.001, p = 0.002; respectively). In contrast to the early postoperative period, total taste sensation was significantly increased in the late postoperative period (p = 0.034). Conclusions: The bitter sensation in the early postoperative period and the bitter and sour sensations in late postoperative period were found to be significantly increased in this present study.With regard to these results, a thorough preoperative explanation should be done.